2021
DOI: 10.3389/fonc.2020.528624
|View full text |Cite
|
Sign up to set email alerts
|

Onco-Esthetics Dilemma: Is There a Role for Electrocosmetic-Medical Devices?

Abstract: ObjectiveThe primary aim of this review is to verify whether the warning against the use of electromedical instruments in the cosmetic professional or medical cancer patient settings is consistent with evident oncological risks supported by experimental in vitro/in vivo studies or anecdotal clinical reports, or any other reasonable statement.MethodsMEDLINE, PubMed, Embase, AMED, Ovid, Cochrane Controlled Trials Register, and Google Scholar databases were electronically searched. Data relating to research desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Palmieri et al. ( 7 ) cite an in vitro study on the effects of ESWT on cancer cells, positing that cell rupture is one of the primary mechanism by which ESWT exerts its effects. Tissue damage has been reported in the literature as a side-effect of high-energy focused ESWT ( 14 ).…”
Section: Extracorporeal Shockwave Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Palmieri et al. ( 7 ) cite an in vitro study on the effects of ESWT on cancer cells, positing that cell rupture is one of the primary mechanism by which ESWT exerts its effects. Tissue damage has been reported in the literature as a side-effect of high-energy focused ESWT ( 14 ).…”
Section: Extracorporeal Shockwave Therapymentioning
confidence: 99%
“…As a result, the importance of supportive care and rehabilitation has grown substantially (3)(4)(5)(6). Palmieri et al (7) recently authored a review of select therapy modalities, with a focus on the array of cosmetic treatment possibilities in cancer patients, as well as their respective safety. The authors concluded that moderate and periodical use of "cosmetic medical devices", including massage, are not contraindicated in cancer patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation